O papel do capital psicológico na relação entre desenho do trabalho, engajamento e rotatividade - Hokama, Erica (2020)
The psychological capital affects the behaviors of workers, as it deals with the specifications of their content, procedures and forms of relationships within the work context, with the aim of generating positive results for the organization, as well as providing job satisfaction. However, other factors, including individual characteristics, such as psychological capital, can also play an important role in these relationships. The general objective of this research was to verify whether psychological capital has a moderating effect on the relationships between the design of work and engagement, and also, between the design of work and the turnover intention, as well as to identify the relationships between these constructs. A field, quantitative, descriptive and cross-sectional research was carried out with 318 participants. The instruments used to evaluate the variables were the Work Design Questionnaire (WDQ), the Utrecht Work Engagement Scale (UWES-9), Turnover Intention Scale (TIS), the Psychological Capital Questionnaire (PCQ) and a Sociodemographic Questionnaire. The data were submitted to descriptive statistical analysis, factor analysis, Cronbach's alpha calculations and linear regression analysis. The results indicated that the design of work and psychological capital are positively related to engagement at work and negatively to the turnover intention. Regression analyzes pointed out the design of work and psychological capital as predictive factors for engagement at work and the turnover intention. In addition, psychological capital is a factor suppressor between specialization and engagement at work and moderator between problem solving and turnover intention. Given these results and so many transformations in the world of work, studying the creation and modification of the composition, contents, structure and environments in which the works and functions are performed (aspects of the design of the work), as well as developing psychological capital is important for companies and workers can prepare themselves for the demands of the labor market. This is the first study in Brazil to integrate the theory of work design with psychological capital, engagement at work and turnover intention. Therefore, in addition to adding theoretical knowledge to the area, it is expected that this research promotes reflections by professionals in the areas of Organizational and Work Psychology, Administration and Human Resource Management, on the importance of developing strategies for “work design” and development of “psychological capital”, in order not only to increase engagement and decrease the turnover intention, but above all to promote health within the work environment.